2014
DOI: 10.1186/1472-6963-14-146
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs of obesity in Thailand: a retrospective cost-of-illness study

Abstract: BackgroundOver the last decade, the prevalence of obesity (BMI ≥ 25 kg/m2) in Thailand has been rising rapidly and consistently. Estimating the cost of obesity to society is an essential step in setting priorities for research and resource use and helping improve public awareness of the negative economic impacts of obesity. This prevalence-based, cost-of-illness study aims to estimate the economic costs of obesity in Thailand.MethodsThe estimated costs in this study included health care cost, cost of productiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 37 publications
4
57
1
4
Order By: Relevance
“…A British cohort study revealed that obesity when young (less than 40 years) was significantly associated with a higher risk of KD incidence (Silverwood et al, 2013). Multiple studies have shown obesity is a risk for KD which then becomes part of the enormous national cost of excess weight (W. Chen et al, 2009;Du et al, 2017;Pitayatienanan et al, 2014;L. Xue et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A British cohort study revealed that obesity when young (less than 40 years) was significantly associated with a higher risk of KD incidence (Silverwood et al, 2013). Multiple studies have shown obesity is a risk for KD which then becomes part of the enormous national cost of excess weight (W. Chen et al, 2009;Du et al, 2017;Pitayatienanan et al, 2014;L. Xue et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thailand's rapid socio-economic development in the last 4 decades leads to urbanization (Lim, Kjellstrom, et al, 2009), and sedentary work. People consume more calories and more fat, sugar and salt (Aekplakorn et al, 2011;Lim et al, 2014;Pitayatienanan et al, 2014). Urbanization altered lifestyle with more alcohol consumption and a higher incidence of non-communicable diseases such as hypertension, high cholesterol and obesity (Wakabayashi et al, 2015).…”
mentioning
confidence: 99%
“…In Asia, several studies have measured productivity changes due to obesity. The cost of productivity losses due to obesity was estimated to be approximately 7 billion Baht (US$390 million) in Thailand in 2009 (20). In New Zealand, the productivity losses due to obesity were equivalent to 1.6% of the total healthcare expenditure in 2005 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Another review in 10 European countries indicated that the cost of obesity is responsible for 0.09%-0.61% of the gross domestic product (Müller-Riemenschneider 2008). Several studies have also examined the economic cost of obesity in Asia-Pacific countries (Ko 2008, Zhao 2008, Pitayatienanan et al 2014, while a recent systematic review (Hoque 2016) identified 13 articles examining the economic burden of obesity in Australia; the People's Republic of China (PRC); Hong Kong, China; Japan, the Republic of Korea; New Zealand; Taipei,China; and Thailand. It revealed that overweight and obesity was responsible for 1.5%-9.9% of their total health expenditures.…”
Section: Introductionmentioning
confidence: 99%